Public Perception Of Noise (Case Study: Malikussaleh University Aksi Adb Project - Adella, Faradya; Gani, Asri; Deli, Anwar (Ridwan Institute, 2024)
Malikussaleh University (Unimal) is one of the four universities selected to get a loan from the Asian Development Bank (ADB) related to the Advanced Knowledge and Skills for Sustainable Growth in Indonesia (AKSI) project. In the construction process, such as installation activities and building infrastructure from equipment, it can trigger unexpected noise, so it can have an impact on people's health and comfort. This research was conducted in five new building construction locations on the Bukit Indah campus of Malikussaleh University. The purpose of this study is to see the perception and attitude of the community around the construction project activities. The research method used was the distribution of questionnaires and using the Likert scale to measure the attitudes, opinions, and perceptions of the research respondents. The results of the questionnaire will be processed using SPSS software. The results showed that the overall average value of the respondents' perception of noise was 2.35. This figure shows that the current place of work/study/living does not feel noisy due to ongoing construction work.